A Comparative Study Of The Curriculum At Ma'arif Sukorejo Islamic Elementary School With The Curriculum At Pager 2 Sengonagung Purwosari Public Elementary School - Ningsih, Sanianisa; Kirom, Askhabul; Hadi, Muhammad Nur (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to compare the curriculum implemented in Ma'arif Sukorejo Islamic Elementary School and Pager 2 Sengonagung Purwosari State Elementary School. Through the analysis of various components of the curriculum, it was found that in the aspect of learning materials. Ma'arif Sukorejo Islamic Primary School presents additional materials that focus on Islamic religious education, such as Al-Qur'an Hadith, Jurisprudence, Islamic Culture History (SKI), Akidah Akhlak, and Ahlussunnah wal Jama'ah (Aswaja). In contrast, Pager 2 State Elementary School provides Islamic Religious Education (PAI) subjects with one additional material for reading and writing the Qur'an (BTQ) only. In addition to differences in material, educational objectives are also a differentiator in this study. Ma'arif Sukorejo Islamic Elementary School emphasizes the formation of students who are not only academically intelligent, but also religious and Islamic. Meanwhile, Pager 2 State Elementary School emphasizes the development of students who are intelligent and have character in accordance with the values of Pancasila. This research uses a qualitative approach with a comparative method, where data is obtained through observation interviews and documentation. The results provide an overview of the similarities and differences in the curriculum components of each school, with a focus on religious materials and learning objectives as the differentiating elements. In conclusion, although the two schools have different focuses, they still implement Merdeka Curriculum as an effort to produce a generation that is smart, creative, characterized, religious, and ready to face future challenges.